Putting public health evidence into practice: increasing the prevalence of working smoke alarms in disadvantaged inner city housing. Issue 4 (16th March 2004) - Roberts, H; Curtis, K; Liabo, K; Rowland, D; DiGuiseppi, C; Roberts, I
Abstract : Study objectives: The UK government recommends that local authorities install battery operated smoke alarms to prevent fire related injury. However, a randomised controlled trial of smoke alarm installation in local authority housing found a low level of working alarms at follow up. Qualitative work, which accompanied the trial explored barriers and levers to the use of this public health intervention. Design: Semi-structured group and individual interviews were conducted with a sample of the adult participants in a randomised controlled trial of free smoke alarm installation. Group interviews and "draw and write" exercises were conducted with children at a local primary school. Participants: A sample of trial participants and primary school children in the trial neighbourhood. Setting: An inner city housing estate in central London. Main results: The main barrier to smoke alarm use was the distress caused by false alarms. Although trial participants considered themselves to be at high risk for fires and would recommend smoke alarms to others, respondents' reports on the distress caused by false alarms suggest that people balance immediate and longer term risks to their health and wellbeing when they disable alarms. Conclusions: This study identified some of the reasons for the low level of functioning smoke alarms, and problems experienced with alarms. The results have implications for the implementation of this public health intervention. The effectiveness of smoke alarm installation could be improved if alarm manufacturers and those responsible for implementation programmes considered ways of tackling the issues raised in this study.